China's Pan-Pearl River Delta : regional cooperation and development - Yeh, Anthony G. O., 1952-; Xu, Jiang, 1968- (Hong Kong University Press, 2011)
Examines regional integration and its barriers in southern China in a comparative framework using perspectives on development and globalization from Europe and North America.